2013
DOI: 10.1038/ejhg.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Novel allelic variants and evidence for a prevalent mutation in URAT1 causing renal hypouricemia: biochemical, genetics and functional analysis

Abstract: Renal hypouricemia (RHUC) is a heterogeneous inherited disorder characterized by impaired tubular uric acid (UA) transport with severe complications, such as acute kidney injury (AKI). Type 1 is caused by a loss-of-function mutation in the SLC22A12 gene (URAT1), type 2 in the SLC2A9 gene (GLUT9). This article describes three Czech families with RHUC type 1. The serum UA in the probands was 0.9, 1.1 and 0.5 mg/dl and expressed as an increase in the fractional excretion of UA (48, 43 and 39%). The sequencing ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 36 publications
4
63
0
Order By: Relevance
“…Differential diagnosis of HX includes all causes of hypouricemia. Similarly low levels of serum uric acid observed in our patients with HX were reported by the authors previously in patients with mutations in SLC22A12 and SLC2A9 genes causing primary renal hypouricemia [21,22]. This rare condition is a hereditary defect in uric acid transporters URAT1 (type 1) and GLUT9 (type 2) localized in proximal tubulus.…”
Section: Discussionsupporting
confidence: 79%
“…Differential diagnosis of HX includes all causes of hypouricemia. Similarly low levels of serum uric acid observed in our patients with HX were reported by the authors previously in patients with mutations in SLC22A12 and SLC2A9 genes causing primary renal hypouricemia [21,22]. This rare condition is a hereditary defect in uric acid transporters URAT1 (type 1) and GLUT9 (type 2) localized in proximal tubulus.…”
Section: Discussionsupporting
confidence: 79%
“…We recently identified and functionally characterized three novel variants in the SLC22A12 gene in Czech RHUC patients [4][5][6]. Our findings of two c.1245_1253del heterozygous individuals in a control cohort of 109 subjects from the Roma population suggested the existence of prevalent variant in this minority population in the Czech Republic.…”
Section: Introductionmentioning
confidence: 78%
“…As stipulated by Stiburkova et al [13] , lack of awareness of RHUC likely allows cases to go undetected. Indeed, patients have been subjected to repeat renal biopsies when hypouricemia was not noticed at first presentation [17] .…”
Section: Discussionmentioning
confidence: 99%
“…Shortly thereafter, mutations in SLC2A9 were described in hypouricemic patients, rendering SLC2A9 another causative gene linked to RHUC [16] . When compared to patients with URAT1 mutations, individuals harbouring homozygous GLUT9 mutations exhibit more pronounced hypouricemia with FE-UA often >150%, and appear to be more vulnerable for exercise-induced AKI and nephrolithiasis [13,16] . Subjects with heterozygous GLUT9 mutations show a wider spectrum of serum UA levels, ranging from 2.0 to 4.5 mg/dl, whereas FE-UA values range from 3.2 to 21.7% in one study from Israel [16] ; these authors concluded that haploinsufficiency results in mild hypouricemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation